Importance of Educational Technology in Teaching and Its Impact on Student Achievement: Exploring the Impact of Educational Technology on Student Achievement (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Today, like never before, the role of educational technology in teaching is of extraordinary significance due to the utilization of data and communication advancements. With the assistance of various applications for distance training, the Internet, instructors, and understudies themselves, they see the upside of educational technology. Educational technology and e-learning can happen in or out of the study hall. It very well may act naturally paced, non-concurrent learning or might be educator driven, synchronous learning. It is suited to distance learning and related to eye to eye teaching, which is named blended learning.